Prevalencia del parasitismo intestinal en pacientes atendidos en el Hospital Santa Isabel - El Porvenir (Trujillo – Perú): 2013-2015 - Cueva Montoya, Rocky Michael (2019)
In Peru, especially soil-transmitted helminth (STH) comes to present prevalence, even more than 90% in places with poor sanitation and difficulties in access to potable water, becoming a public health problem, as well as causing problems in nutritional status and nutrient utilization, conditioning diarrheas, anemias, and chronic child malnutrition. Intestinal parasitism is a public health problem in Peru, presenting higher prevalence than 90% in places with poor sanitation and causes problems in nutritional status, and its easy mode of transmission regardless of age, sex or race. For this reason, the present study aims to determine the prevalence of intestinal parasites in patients treated at Hospital Santa Isabel - El Porvenir (Trujillo - Peru): 2013-2015. Analysis of 790 patients with clinical suspicion of intestinal parasitism treated at the Hospital Santa Isabel - El Porvenir - Trujillo, during the years 2013-2105, analyzed by microscopic examination and Graham test were recorded. The 35.7% has some type of intestinal parasite. The most frequent was protozoa Giardia lamblia (27.3%) while the helminth with the highest prevalence was Enterobius vermicularis (7.3%). There was a higher percentage of parasitism in children aged 0-15 years in the three years evaluated.